3D Dirac Semimetal Supported Tunable Multi‐Frequency Terahertz Metamaterial Absorbers - Liu, Shilin; Cao, Wenhan; Jiang, Shizeng; He, Lianhao; Lin, Fangting; He, Xiaoyong (Advanced quantum technologies (Online), 2024)
In recent years, 3D Dirac semimetals (DSM) with linear energy‐momentum dispersion near the Fermi points have emerged as promising material candidates for novel tunable metamaterial devices due to their prominent electromagnetic performance and excellent tunability. In this work, the propagation characteristics of 3D DSM‐supported double and triple stripe patterned metamaterial absorbers (MMAs) are investigated in the terahertz (THz) regime by facile modulation of the Fermi level. The results manifest that for the double stripe patterned devices, two strong absorption peaks with near unity are observed at 0.97 THz and 1.63 THz, respectively. When the Fermi level varies in the range of 0.01–0.15 eV, the amplitude (frequency) modulation depth of resonance is up to 77% (27.3%). Additionally, triple stripe MMAs supported by 3D DSM are devised, which can achieve resonant absorption peaks at three specific frequencies of 0.23, 0.345, and 0.46 THz, while the amplitudes of the peaks are as high as 0.997, 0.940, and 0.779, respectively. Furthermore, the resonances can also be regulated, and the amplitude MD reaches ≈20%. These results are very helpful in understanding the tuning mechanisms of metamaterial devices and aiding the design of THz functional devices, such as receivers, detectors, and modulators. A tunable multi‐frequency terahertz (THz) metamaterial absorber with 3D Dirac semimetal stripes, which operates at three atmospheric windows simultaneously, i.e. 0.23, 0.345, and 0.46 THz is proposed. The perfect absorption peaks can be achieved with a Q‐factor >40. By adjusting the Fermi level, the resonant amplitude and frequency modulation depths are 77.0% and 27.3%, respectively.